A New Approach to Evaluate Regular Semirings in terms of Bipolar Fuzzy k-Ideals Using k-Products - Shahida Bashir; Ahmad N. Al-Kenani; Tanzila Kausar; Rabia Mazhar (Journal of Mathematics, 2022)
In this paper, we provide a generalized form of ideals that is k-ideals of semirings with the combination of a bipolar fuzzy set (BFS). The BFS is a generalization of fuzzy set (FS) that deals with uncertain problems in both positive and negative aspects. The main theme of this paper is to present the idea of α,β-bipolar fuzzy k-subsemiring (k-BFSS), α,β-bipolar fuzzy k-ideals (k-BFIs), and α,β-bipolar fuzzy k-bi-ideals (k-BFbIs) in semirings by applying belongingness ∈ and quasi-coincidence q of the bipolar fuzzy (BF) point. After that, upper and lower parts of k-product of BF subsets of semirings are introduced. Lastly, the notions of k-regular and k-intraregular semirings in terms of ∈,∈∨q-k–BFIs and ∈,∈∨q-k–BFbIs are characterized.